Dysregulation of Retinal Melatonin Biosynthetic Pathway and Differential Expression of Retina-Specific Genes Following Blast-Induced Ocular Injury in Ferrets - Chetan Pundkar; Rex Jeya Rajkumar Samdavid Thanapaul; Manoj Govindarajulu; Gaurav Phuyal; Joseph B. Long; Peethambaran Arun (Neurology International)
Background/Objectives: Blast-induced traumatic ocular injuries (bTOI) pose a significant risk to military and civilian populations, often leading to visual impairment or blindness. Retina, the innermost layer of ocular tissue consisting of photoreceptor and glial cells, is highly susceptible to blast injuries. Despite its prevalence, the molecular mechanisms underlying retinal damage following bTOI remain poorly understood, hindering the development of targeted therapies. Melatonin, a neuroprotective indoleamine with antioxidant, anti-inflammatory, and circadian regulatory properties, is synthesized in the retina and plays a crucial role in retinal health. Similarly, retina-specific genes, such as Rhodopsin, Melanopsin, and RPE65, are essential for photoreceptor function, visual signaling, and the visual cycle. However, their responses to blast exposure have not been thoroughly investigated. Methods: In this study, we utilized a ferret model of bTOI to evaluate the temporal expression of melatonin-synthesizing enzymes, such as tryptophan hydroxylase 1 and 2 (TPH1 and TPH2), Aralkylamine N-acetyltransferase (AANAT), and Acetylserotonin-O-methyltransferase (ASMT), and retina-specific genes (Rhodopsin, Melanopsin) and retinal pigment epithelium-specific 65 kDa protein (RPE65) at 4 h, 24 h, 7 days, and 28 days post-blast. Ferrets were exposed to tightly coupled blast overpressure waves using an advanced blast simulator, and retinal tissues were collected for quantitative polymerase chain reaction (qPCR) analysis. Results: The results revealed dynamic and multiphasic transcriptional responses. TPH1 and TPH2 exhibited significant upregulation at 24 h, followed by downregulation at 28 days, indicating blast-induced dysregulation of tryptophan metabolism, including melatonin synthesis. Similarly, AANAT and ASMT showed acute downregulation post-blast, with late-phase disruptions. Rhodopsin expression increased at 24 h but declined at 28 days, while Melanopsin and RPE65 demonstrated early upregulation followed by downregulation, reflecting potential disruptions in circadian regulation and the visual cycle. Conclusions: These findings highlight the complex regulatory mechanisms underlying retinal responses to bTOI, involving neuroinflammation, oxidative stress, and disruptions in melatonin synthesis and photoreceptor cell functions. The results emphasize the therapeutic potential of melatonin in mitigating retinal damage and preserving visual function.